Enhancing collaborative sketching activities with context-aware adaptation guidelines - Motti, Vivian Genaro; Sangiorgi, Ugo Braga; Vanderdonckt, Jean (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Designing interactive systems for multiple contexts of use becomes a burden when the end user interaction takes place in distinct scenarios whose specific characteristics and constraints vary and must be carefully considered. Stakeholders face then two main challenges: they are not aware of what among several context information is significantly relevant to consider, or how to appropriately adapt the user interfaces according to the information considered. Furthermore, stakeholders cannot simply rely on existing UI editors once they usually do not provide enough support for adaptation. Thus, adaptation is often ignored, resulting in user interfaces that are only suitable for static and conventional contexts of use. To support the design of user interfaces that are properly adapted to their target context, this paper proposes a novel methodology to enhance sketching activities by proposing to the end user context-aware adaptation guidelines. This work aims at raising awareness about context-aware adaptation since the early stages of the UI design.